A strategic model for firms who seek to embrace nanomanufacturing. (19th September 2008) - Tierney, Robert; Walsh, Steven
The term 'nanotechnology' has captured the technological and economic interest of technologists and business professionals alike. The commercial interest in nanotechnology is overwhelming and the term often misrepresented. This is especially evident in nanotechnology market projections, which have risen dramatically over the past 5-10 years as more and more traditional 'product families' are engulfed by the diffusion terminology and then are included in these projections. Nanomanufacturing is seen as a potential Schumpeterian or Kondratief waves (Schumpeter, 1934, 1942; Kondratief, 1937); yet manufacturing processes have been shown to be greatly different in various industrial sectors. The hurdles and problems facing the companies are as diverse as those sectors. This paper seeks to make a contribution by offering a categorisation scheme for nanomanufacturing based on the types of hurdles that firms are quite likely to encounter and provide some case base examples of both evolutionary and revolutionary nanomanufactured products.